2018
DOI: 10.1108/imefm-08-2017-0212
|View full text |Cite
|
Sign up to set email alerts
|

Principal-agent relationship issues in Islamic banks: a view of Islamic ethical system

Abstract: Purpose This paper aims to discuss and explore the unique agency issues in Islamic banks which give rise to different agency conflicts exist in Islamic banks as compared to conventional banks. In addition, this paper critically examines agency theory in Islamic banking perspective by incorporating Islamic ethical considerations in the principal–agent setting. Design/methodology/approach This is a conceptual paper, and the discussions revolve around the review of literature of which important sources have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 38 publications
0
31
0
3
Order By: Relevance
“…The findings in this study do not support the research conducted by Khalid et al, (2017) which indicated that work programs have a positive effect on the effectiveness of sharia supervision. The findings in this study, according to Rahman (2008) in Khalid et al, (2017), appear to indicate that sharia supervision in Islamic banks is not currently implemented comprehensively, and fails to cover all the problems with sharia in the financial, social, organizational structure, and management ethics aspects (Khalid et al, 2017;Zainuldin et al, 2018).…”
Section: Hypothesis Testingmentioning
confidence: 70%
See 2 more Smart Citations
“…The findings in this study do not support the research conducted by Khalid et al, (2017) which indicated that work programs have a positive effect on the effectiveness of sharia supervision. The findings in this study, according to Rahman (2008) in Khalid et al, (2017), appear to indicate that sharia supervision in Islamic banks is not currently implemented comprehensively, and fails to cover all the problems with sharia in the financial, social, organizational structure, and management ethics aspects (Khalid et al, 2017;Zainuldin et al, 2018).…”
Section: Hypothesis Testingmentioning
confidence: 70%
“…Sharia compliance thus reflects the prinsciple of halal transactions in Islamic banks, discarding the elements of usury, gharar, maysir, and zalim. For Muslims, sharia compliance in their economic activities satisfies a spiritual need by protecting their property from prohibited deeds (Zainuldin et al, 2018).…”
Section: Sharia Compliancementioning
confidence: 99%
See 1 more Smart Citation
“…Some authors think that Islamic ethics is the answer to all governance problems and that there is no need to look further. Zainuldin et al (2018), after elaborating on the various governance problems in Islamic banks, blithely state that consultative consultation, that is allowing all stakeholders to contribute to the decision-making process, is the way to ensure that Islamic ethics rule the process so that everybody takes account of other peoples' interests and no dishonesty will occur. As Islamic ethics is based on presumed divine revelation, it is important to support any proposal with references to the prophet Muhammad and Zainuldin et al argue that consultative (shuratic) decisionmaking characterized the leadership of the prophet and the caliphs (the worldly and spiritual leaders of the Muslim community) after him.…”
Section: (A) Esg (Environmental Social and Governance)mentioning
confidence: 99%
“…Ti dak ada keterpisahan antara satu dengan yang lainnya. Konsep inilah yang peneliti ba ngun dalam membentuk etika profesi penge lola keuangan negara dan membedakannya dengan penelitian lain sebagaimana kajian yang dilakukan oleh Afou (2017), Zainuldin et al (2018), dan Zubairu et al (2019) yang memotret etika profesi akuntan dalam per spektif Islam semata tanpa melibatkan re alitas spiritual sebagai konsep deep ecology dalam kajiannya.…”
unclassified